Low-temperature sodium-based liquid metal battery and preparation method thereof
By using inorganic composite molten salt electrolyte in liquid metal batteries, adjusting the mole percentage of halides, reducing the operating temperature of the battery, solving the problems of high thermal management costs and short life of existing liquid metal batteries, and achieving more efficient and safe battery performance.
Patent Information
- Application Number
- CN202510087898.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-21
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2045-01-21
AI Technical Summary
Due to the high working temperature of existing liquid metal batteries, the thermal management cost is high, the lifespan is short, and the low melting point of the electrolyte is difficult to achieve.
Inorganic composite molten salt electrolytes are used, including cesium halide salt, potassium halide salt, sodium halide salt, lithium halide salt, etc. By adjusting the molar percentage of these salts, the melting point of the electrolyte is significantly reduced, so that the battery can operate at a lower temperature of 270-370°C.
It reduces the operating temperature of the battery, reduces the power consumption of the thermal management system, extends the life of the battery insulation sealing material, and improves the cycle life and safety of the battery.
Smart Images

Figure CN119833783A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of energy storage batteries, and in particular, relates to a low-temperature sodium-based liquid metal battery and a preparation method thereof. Background Art
[0002] Traditional lithium-ion batteries face difficult-to-solve problems such as performance degradation, high cost, and poor safety in large-scale energy storage. Liquid metal batteries are a new type of electrochemical energy storage device that uses molten metals / alloys as electrodes and inorganic molten salts as electrolytes. Due to the large density difference and immiscibility between the electrodes and the electrolyte, a unique three-layer liquid structure will spontaneously form inside the battery. The upper layer is an alkali metal or alkaline earth metal with low density (such as Li, Na, K, Mg, Ca, etc.), the middle layer is an inorganic molten salt electrolyte, and the lower layer is a metal with high density and high electronegativity (such as Sb, Pb, Sn, Bi, Te, etc.). This liquid electrode has an amorphous structure, which can effectively avoid dendrite growth, and can self-repair the mechanical damage suffered by the electrode during the cycle process. It has a "self-healing" characteristic, so it has an ultra-long life limit and is very suitable for large-scale static energy storage at the grid level. However, in order to meet the melting point of both the electrode and the electrolyte, liquid metal batteries need to operate at high temperatures, which has become its much-criticized shortcoming. For example, the current competitive liquid metal battery systems such as Li||Sb-Pb, Li||Sb-Sn, Li||Bi, Li||Sb, Ca-Mg||Bi Na||Sb-Sn, etc. have an operating temperature of 480-550oC. Limited by the lack of Li resources and the severe corrosion caused by the high operating temperature, the long-term stable service of liquid metal batteries on a large scale still faces huge challenges. Metal Na has a low melting point (97.8℃), a low density (0.93g / cm 3 ), has good compatibility with sealing materials such as Al2O3, and the abundance of Na in the earth's crust reaches 2.83%wt, and the resources are abundant. Sodium-based liquid metal batteries have great potential to achieve low operating temperature, low cost and long life, and have broad application prospects in the field of large-scale energy storage. Therefore, it is of great theoretical and practical significance to develop a liquid metal battery with low cost and low operating temperature.
[0003] In order to realize the operation of sodium-based liquid metal batteries at lower temperatures, the negative electrode, positive electrode, and electrolyte must meet the melting point requirements at the same time. Usually, the negative electrode uses metal Na, which has a melting point of 98°C and is in liquid state at the operating temperature, which is a non-limiting factor. For the positive electrode, there are a series of low-melting-point, cheap, and high-specific-energy materials such as Bi-Sn (eutectic point 141°C), Bi-Pb (eutectic point 125°C), Sb-Pb (252°C), and Sn-Pb (182°C), so they do not constitute a limiting factor. However, electrolytes with low melting points, strong adaptability, and stable chemical properties are actually very difficult to find. For example, the melting point of Na2CO3-NaCl eutectic salt is 637°C, and the melting point of NaF-NaCl-NaI eutectic salt is 501°C. Considering that the melting point of a single sodium ion electrolyte is difficult to lower, some researchers have proposed the use of multi-cation composite electrolytes, such as adding lithium halides and potassium halides. Zhou et al. reported that a liquid metal battery using LiCl-NaCl-KCl (melting point 390°C) as electrolyte can operate at 450°C (Energy Storage Materials, 2022, 50:572–579.). However, its operating temperature is still relatively high, so the electrolyte needs to be further optimized to reduce its operating temperature. Summary of the invention
[0004] In view of the defects of the prior art, the present invention provides a low-temperature sodium-based liquid metal battery and a preparation method thereof, the purpose of which is to lower the operating temperature of the battery, increase the life of the liquid metal battery, and reduce additional thermal management power consumption.
[0005] According to a first aspect of the present invention, a sodium-based liquid metal battery is provided, comprising a negative electrode, an electrolyte, and a positive electrode; the negative electrode is sodium or a sodium alloy; the electrolyte is an inorganic composite molten salt electrolyte, the inorganic composite molten salt electrolyte comprises a cesium halide salt, and further comprises two or more salts of a potassium halide salt, a sodium halide salt, a lithium halide salt, and a rubidium halide salt, and the molar percentage of the cesium halide salt in the electrolyte is 10% to 30%.
[0006] Preferably, the potassium halide salt is selected from one or more of KCl, KBr, and KI; the sodium halide salt is selected from one or more of NaCl, NaBr, and NaI; the lithium halide salt is selected from one or more of LiCl, LiBr, and LiI; the cesium halide salt is selected from one or more of CsCl, CsBr, and CsI; the rubidium halide salt is selected from one or more of RbCl, RbBr, and RbI.
[0007] Preferably, the inorganic composite molten salt electrolyte is a mixture of KCl, NaCl, and CsCl, wherein the molar percentage of KCl is 30-50%, the molar percentage of NaCl is 20-40%, and the molar percentage of CsCl is 10-30%; or the inorganic composite molten salt electrolyte is a mixture of RbCl, KCl, and CsCl, wherein the molar percentage of RbCl is 20-40%, the molar percentage of KCl is 30-50%, and the molar percentage of CsCl is 10-30%; or the inorganic composite molten salt electrolyte is a mixture of NaCl, LiBr, and CsCl, wherein the molar percentage of NaCl is 20-40%, the molar percentage of LiBr is 30-50%, and the molar percentage of CsCl is 10-30%. The molar percentage of sCl is 10-30%; or the inorganic composite molten salt electrolyte is a mixture of LiCl, KI, and CsI, wherein the molar percentage of LiCl is 20-40%, the molar percentage of KI is 30-50%, and the molar percentage of CsI is 10-30%; or the inorganic composite molten salt electrolyte is a mixture of NaCl, KBr, and CsBr, wherein the molar percentage of NaCl is 20-40%, the molar percentage of KBr is 30-50%, and the molar percentage of CsBr is 10-30%; or the inorganic composite molten salt electrolyte is a mixture of KI, LiBr, NaI, and CsCl, wherein the molar percentage of KI is 20-40%, the molar percentage of LiBr is The molar percentage of NaI is 20-60%, the molar percentage of NaI is 10-30%, and the molar percentage of CsCl is 10-30%; or the inorganic composite molten salt electrolyte is a mixture of KI, LiBr, NaBr, and CsCl, wherein the molar percentage of KI is 20-40%, the molar percentage of LiBr is 20-40%, the molar percentage of NaBr is 10-30%, and the molar percentage of CsCl is 10-30%; or the inorganic composite molten salt electrolyte is a mixture of KI, LiBr, NaI, and CsI, wherein the molar percentage of KI is 20-40%, the molar percentage of LiBr is 20-60%, the molar percentage of NaI is 10-30%, and the molar percentage of CsI is 1 0-30%; or the inorganic composite molten salt electrolyte is a mixture of KCl, CsCl, NaBr, and RbCl, wherein the molar percentage of KCl is 20-40%, the molar percentage of CsCl is 10-30%, the molar percentage of NaBr is 10-30%, and the molar percentage of RbCl is 10-30%; or the inorganic composite molten salt electrolyte is a mixture of KCl, LiCl, LiBr, NaCl, and CsCl, wherein the molar percentage of KCl is 20-40%, the molar percentage of LiCl is 10-40%, the molar percentage of LiBr is 10-40%, the molar percentage of NaCl is 10-30%, and the molar percentage of CsCl is 10-30%;Or the inorganic composite molten salt electrolyte is a mixture of KBr, LiBr, LiI, NaBr, and CsBr, wherein the molar percentage of KBr is 20-40%, the molar percentage of LiBr is 10-40%, the molar percentage of LiI is 10-40%, the molar percentage of NaBr is 10-30%, and the molar percentage of CsBr is 10-30%; or the inorganic composite molten salt electrolyte is a mixture of KI, LiBr, LiI, NaI, and CsI, wherein the molar percentage of KI is 20-40%, the molar percentage of LiBr is 10-40%, the molar percentage of LiI is 10-40%, the molar percentage of NaI is 10-30%, and the molar percentage of CsI is 10-30%. ;
[0008] Preferably, the sodium alloy is selected from Na-K, Na-In, Na-Al or Na-Zn, and the molar percentage of sodium in the sodium alloy is greater than 40%-90%.
[0009] Preferably, the material of the positive electrode is selected from an alloy consisting of two or more elements of Bi, Cd, Sn and Pb.
[0010] Preferably, the positive electrode is a Bi, Sn alloy, wherein the molar percentage of Bi is 10-90%; or the positive electrode is a Bi, Pb, Cd alloy, wherein the molar percentage of Bi is 50-60%, the molar percentage of Pb is 10-30%, and the molar percentage of Cd is 10-30%; or the positive electrode is a Bi, Pb, Sn alloy, wherein the molar percentage of Bi is 50-60%, the molar percentage of Pb is 20-30%, and the molar percentage of Sn is 10-30%; or the positive electrode is a Bi, Pb, Sn, Cd alloy, wherein the molar percentage of Bi is 50-60%, the molar percentage of Pb is 20-30%, the molar percentage of Sn is 10-20%, and the molar percentage of Cd is 10-20%.
[0011] Preferably, the operating temperature of the battery is 270-370° C., and the negative electrode, electrolyte and positive electrode are all in liquid state at the operating temperature.
[0012] According to another aspect of the present invention, a method for preparing the sodium-based liquid metal battery is provided, and the specific preparation steps are as follows:
[0013] (1) preparing a positive electrode alloy material, and placing the positive electrode alloy material in a shell to prepare a positive electrode;
[0014] (2) melting the electrolyte and pouring it into the positive electrode so that the electrolyte is in a molten state;
[0015] (3) placing the negative electrode current collector adsorbed with sodium or sodium alloy in a molten electrolyte and submerging it in the electrolyte;
[0016] (4) Assembling the top cover on the shell and welding it to obtain a sodium-based liquid metal battery; wherein steps (1) to (4) are all carried out under the protection of a protective gas.
[0017] Preferably, the negative electrode current collector is selected from foamed nickel iron or foamed aluminum.
[0018] In general, the above technical solution conceived by the present invention has the following technical advantages compared with the prior art:
[0019] (1) The present invention innovatively introduces cesium halide salts (such as CsCl, CsBr, CsI) into the electrolyte of the liquid metal battery. By precisely adjusting the molar percentage of the cesium halide salt to 10% to 30%, the melting point of the electrolyte is significantly reduced without sacrificing the stability of the electrolyte, so that the liquid metal battery can operate at a lower temperature of 270 to 370°C. The lower operating temperature not only greatly reduces the power consumption of the thermal management system, but also effectively extends the life of the battery insulation sealing material.
[0020] (2) By rationally considering and optimizing the amount of each substance in the electrolyte, the molar percentage of other halides is precisely controlled to ensure that the electrolyte has high ion mobility, excellent fluidity and chemical stability at low temperatures, significantly improving the cycle life and safety of the battery. At the same time, a dynamic multi-component compounding technology is proposed, which allows the formulation to be optimized in real time according to specific application requirements.
[0021] (3) The negative electrode sodium alloy of the present invention includes but is not limited to Na-K, Na-In, Na-Al or Na-Zn alloys, and the positive electrode material is selected from an alloy composed of two or more elements of Bi, Cd, Sn, and Pb. The melting point and electrochemical properties are further optimized by adjusting the alloy ratio.
[0022] (4) The electrolyte system of the present invention has the characteristics of low-temperature high performance, environmental protection and economy, and wide applicability, and is suitable for a variety of application scenarios such as large-scale energy storage, low-temperature extreme environments, and high power output. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is the DSC (melting point) test of the electrolyte battery described in Example 1 before cycling.
[0024] Figure 2 This is the DSC (melting point) test of the electrolyte battery described in Example 2 before cycling.
[0025] Figure 3This is the DSC (melting point) test of the electrolyte battery described in Example 3 before cycling.
[0026] Figure 4 This is the DSC (melting point) test of the electrolyte battery described in Example 4 before cycling.
[0027] Figure 5 3 is the discharge curve of the battery described in Example 2 at 350°C.
[0028] Figure 6 This is the cycle curve of the battery described in Example 2 at 350°C. DETAILED DESCRIPTION
[0029] In order to make the purpose, technical scheme and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.
[0030] Example 1
[0031] A liquid metal battery is produced by the following steps:
[0032] (1) Under inert gas protection, weigh 14.5 g of bismuth particles and 13.2 g of tin particles and place them in a graphite crucible (inner diameter 56 mm);
[0033] (2) Under the protection of inert gas, the graphite crucible is heated to 300° C. on a heating plate and kept at this temperature for 2 hours to melt the metal bismuth and the metal tin to form an alloy; then the crucible is naturally cooled to room temperature, and then the graphite crucible is placed in a stainless steel shell of a matching size;
[0034] (3) Under the protection of inert gas, 2.7 g of liquid metal Na was absorbed by aluminum foam as the negative electrode;
[0035] (4) Under inert gas protection, 65 g of dry KI 27 -LiBr 53 -NaI 10 -CsCl 10 ,Depend on Figure 1 It can be seen that the melting point of the electrolyte is 313°C. The mixed salt is heated and melted and poured into the aforementioned graphite crucible;
[0036] (5) Under the protection of inert gas, assemble the negative electrode current collector foam aluminum adsorbed with metal and the top cover onto the shell to which the molten salt (not solidified) has been added, and then cool naturally to room temperature;
[0037] (6) Welding the shell and the top cover by laser welding or argon arc welding to obtain an assembled battery;
[0038] (7) The battery is placed in a test furnace, heated to the operating temperature and maintained at a constant temperature, and connected to a battery test system for battery testing.
[0039] Example 2
[0040] A liquid metal battery is produced by the following steps:
[0041] (1) Under inert gas protection, weigh 38.98 g of bismuth particles, 5.52 g of lead particles, and 9.49 g of tin particles and place them in a graphite crucible (inner diameter 56 mm);
[0042] (2) under the protection of inert gas, the graphite crucible is heated to 400° C. on a heating plate and kept at this temperature for 2 hours to melt the metal bismuth, metal lead and metal tin to form an alloy; then the crucible is naturally cooled to room temperature, and then the graphite crucible is placed in a stainless steel shell of a matching size;
[0043] (3) Under the protection of inert gas, 10.5 g of liquid metal Na was absorbed by nickel foam as the negative electrode;
[0044] (4) Under inert gas protection, 180 g of dry KI 27 -LiBr 53 -NaI 10 -CsI 10 ,Depend on Figure 2 It can be seen that the melting point of the electrolyte is 330°C. The mixed salt is heated and melted and poured into the aforementioned graphite crucible;
[0045] (5) Under the protection of inert gas, assemble the negative electrode current collector foam aluminum adsorbed with metal and the top cover onto the shell to which the molten salt (not solidified) has been added, and then cool naturally to room temperature;
[0046] (6) Welding the shell and the top cover by laser welding or argon arc welding to obtain an assembled battery;
[0047] (7) The battery is placed in a test furnace, heated to the operating temperature and maintained at a constant temperature, and connected to a battery test system for battery testing. The prepared battery is subjected to a charge and discharge test at 350°C to obtain a discharge curve, such as Figure 5 As shown in the figure, it can be seen that the battery can operate stably at this temperature; the prepared battery was subjected to a cycle test at 350°C to obtain a cycle curve, as shown in Figure 6 As shown in the figure, it can be seen that the battery runs for more than 125 cycles and the coulomb efficiency reaches 99%.
[0048] Example 3
[0049] A liquid metal battery is produced by the following steps:
[0050] (1) Under the protection of inert gas, weigh 14.5 g of bismuth particles, 8 g of lead particles, and 5 g of tin particles, and place them in a graphite crucible (inner diameter 56 mm);
[0051] (2) under the protection of inert gas, the graphite crucible is heated to 400° C. on a heating plate and kept at this temperature for 2 hours to melt the metal bismuth, metal lead and metal tin to form an alloy; then the crucible is naturally cooled to room temperature, and then the graphite crucible is placed in a stainless steel shell of a matching size;
[0052] (3) Under the protection of inert gas, 2.7 g of liquid metal Na was absorbed by aluminum foam as the negative electrode;
[0053] (4) Under inert gas protection, 65 g of dry KI 24 -LiBr 28 -NaBr 28 -CsCl 20 ,Depend on Figure 3 It can be seen that the lowest melting point of this system is 276°C. The mixed salt is heated to melt and poured into the aforementioned graphite crucible;
[0054] (5) Under the protection of inert gas, assemble the negative electrode current collector foam aluminum adsorbed with metal and the top cover onto the shell to which the molten salt (not solidified) has been added, and then cool naturally to room temperature;
[0055] (6) Welding the shell and the top cover by laser welding or argon arc welding to obtain an assembled battery;
[0056] (7) The battery is placed in a test furnace, heated to the operating temperature and maintained at a constant temperature, and connected to a battery test system for battery testing.
[0057] Example 4
[0058] A liquid metal battery is produced by the following steps:
[0059] (1) Under inert gas protection, weigh 5.77 g of bismuth particles, 3.08 g of lead particles, 0.85 g of tin particles, and 0.29 g of cadmium particles, and place them in a graphite crucible (inner diameter 56 mm);
[0060] (2) under the protection of inert gas, the graphite crucible is heated to 400° C. on a heating plate and kept at this temperature for 2 hours to melt the metal bismuth, metal lead and metal tin to form an alloy; then the crucible is naturally cooled to room temperature, and then the graphite crucible is placed in a stainless steel shell of a matching size;
[0061] (3) Under the protection of inert gas, 2.7 g of liquid metal Na was absorbed by aluminum foam as the negative electrode;
[0062] (4) Under inert gas protection, 40 g of dry KCl 24 -CsCl 28 -NaBr 28 -RbCl 20 ,Depend on Figure 4 It can be seen that the lowest melting point of this system is 265°C. The mixed salt is heated to melt and poured into the aforementioned graphite crucible;
[0063] (5) Under the protection of inert gas, assemble the negative electrode current collector foam aluminum adsorbed with metal and the top cover onto the shell to which the molten salt (not solidified) has been added, and then cool naturally to room temperature;
[0064] (6) Welding the shell and the top cover by laser welding or argon arc welding to obtain an assembled battery;
[0065] (7) The battery is placed in a test furnace, heated to the operating temperature and maintained at a constant temperature, and connected to a battery test system for battery testing.
[0066] It will be easily understood by those skilled in the art that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A sodium-based liquid metal battery, characterized in that: It includes a negative electrode, an electrolyte, and a positive electrode; the negative electrode is sodium or a sodium alloy; the electrolyte is an inorganic composite molten salt electrolyte, the inorganic composite molten salt electrolyte includes a cesium halide salt, and also includes two or more salts of a potassium halide salt, a sodium halide salt, a lithium halide salt, and a rubidium halide salt, and the molar percentage of the cesium halide salt in the electrolyte is 10% to 30%.
2. A sodium-based liquid metal battery according to claim 1, characterized in that: The potassium halide salt is selected from one or more of KCl, KBr, and KI; the sodium halide salt is selected from one or more of NaCl, NaBr, and NaI; the lithium halide salt is selected from one or more of LiCl, LiBr, and LiI; the cesium halide salt is selected from one or more of CsCl, CsBr, and CsI; the rubidium halide salt is selected from one or more of RbCl, RbBr, and RbI.
3. A sodium-based liquid metal battery according to claim 2, characterized in that: The inorganic composite molten salt electrolyte is a mixture of KCl, NaCl and CsCl, wherein the molar percentage of KCl is 30-50%, the molar percentage of NaCl is 20-40%, and the molar percentage of CsCl is 10-30%; Or the inorganic composite molten salt electrolyte is a mixture of RbCl, KCl and CsCl, wherein the molar percentage of RbCl is 20-40%, the molar percentage of KCl is 30-50%, and the molar percentage of CsCl is 10-30%; Or the inorganic composite molten salt electrolyte is a mixture of NaCl, LiBr and CsCl, wherein the molar percentage of NaCl is 20-40%, the molar percentage of LiBr is 30-50%, and the molar percentage of CsCl is 10-30%; Or the inorganic composite molten salt electrolyte is a mixture of LiCl, KI and CsI, wherein the molar percentage of LiCl is 20-40%, the molar percentage of KI is 30-50%, and the molar percentage of CsI is 10-30%; Or the inorganic composite molten salt electrolyte is a mixture of NaCl, KBr and CsBr, wherein the molar percentage of NaCl is 20-40%, the molar percentage of KBr is 30-50%, and the molar percentage of CsBr is 10-30%; Or the inorganic composite molten salt electrolyte is a mixture of KI, LiBr, NaI, and CsCl, wherein the molar percentage of KI is 20-40%, the molar percentage of LiBr is 20-60%, the molar percentage of NaI is 10-30%, and the molar percentage of CsCl is 10-30%; Or the inorganic composite molten salt electrolyte is a mixture of KI, LiBr, NaBr and CsCl, wherein the molar percentage of KI is 20-40%, the molar percentage of LiBr is 20-40%, the molar percentage of NaBr is 10-30% and the molar percentage of CsCl is 10-30%; Or the inorganic composite molten salt electrolyte is a mixture of KI, LiBr, NaI, and CsI, wherein the molar percentage of KI is 20-40%, the molar percentage of LiBr is 20-60%, the molar percentage of NaI is 10-30%, and the molar percentage of CsI is 10-30%; Or the inorganic composite molten salt electrolyte is a mixture of KCl, CsCl, NaBr, and RbCl, wherein the molar percentage of KCl is 20-40%, the molar percentage of CsCl is 10-30%, the molar percentage of NaBr is 10-30%, and the molar percentage of RbCl is 10-30%; Or the inorganic composite molten salt electrolyte is a mixture of KCl, LiCl, LiBr, NaCl, and CsCl, wherein the molar percentage of KCl is 20-40%, the molar percentage of LiCl is 10-40%, the molar percentage of LiBr is 10-40%, the molar percentage of NaCl is 10-30%, and the molar percentage of CsCl is 10-30%; Or the inorganic composite molten salt electrolyte is a mixture of KBr, LiBr, LiI, NaBr, and CsBr, wherein the molar percentage of KBr is 20 to 40%, the molar percentage of LiBr is 10 to 40%, the molar percentage of LiI is 10 to 40%, the molar percentage of NaBr is 10 to 30%, and the molar percentage of CsBr is 10 to 30%; Or the inorganic composite molten salt electrolyte is a mixture of KI, LiBr, LiI, NaI, and CsI, wherein the molar percentage of KI is 20-40%, the molar percentage of LiBr is 10-40%, the molar percentage of LiI is 10-40%, the molar percentage of NaI is 10-30%, and the molar percentage of CsI is 10-30%.
4. A sodium-based liquid metal battery according to claim 1, characterized in that: The sodium alloy is selected from Na-K, Na-In, Na-Al or Na-Zn, and the molar percentage of sodium in the sodium alloy is 40%-90%.
5. A sodium-based liquid metal battery according to claim 1, characterized in that: The material of the positive electrode is selected from an alloy consisting of two or more elements of Bi, Cd, Sn and Pb.
6. A sodium-based liquid metal battery according to claim 5, characterized in that: The positive electrode is a Bi, Sn alloy, wherein the molar percentage of Bi is 10-90%; or the positive electrode is a Bi, Pb, Cd alloy, wherein the molar percentage of Bi is 50-60%, the molar percentage of Pb is 10-30%, and the molar percentage of Cd is 10-30%; or the positive electrode is a Bi, Pb, Sn alloy, wherein the molar percentage of Bi is 50-60%, the molar percentage of Pb is 20-30%, and the molar percentage of Sn is 10-30%; or the positive electrode is a Bi, Pb, Sn, Cd alloy, wherein the molar percentage of Bi is 50-60%, the molar percentage of Pb is 20-30%, the molar percentage of Sn is 10-20%, and the molar percentage of Cd is 10-20%.
7. A sodium-based liquid metal battery according to claim 1, characterized in that: The operating temperature of the battery is 270-370° C., and the negative electrode, electrolyte and positive electrode are all in liquid state at the operating temperature.
8. A method for preparing a sodium-based liquid metal battery according to any one of claims 1 to 7, characterized in that: The specific preparation steps are: (1) preparing a positive electrode alloy material, and placing the positive electrode alloy material in a shell to prepare a positive electrode; (2) melting the electrolyte and pouring it into the positive electrode so that the electrolyte is in a molten state; (3) placing the negative electrode current collector adsorbed with sodium or sodium alloy in a molten electrolyte and submerging it in the electrolyte; (4) Assembling the top cover on the shell and welding it to obtain a sodium-based liquid metal battery; wherein steps (1) to (4) are all carried out under the protection of a protective gas.
9. The method for preparing a sodium-based liquid metal battery according to claim 8, characterized in that: The negative electrode current collector is selected from foamed iron nickel or foamed aluminum.
Citation Information
Patent Citations
Low-temperature liquid metal battery and preparation method thereof
CN114792847A
Sodium-based liquid metal battery based on replacement reaction and preparation method thereof
CN114824512A
Electrochemical heat engine
US4090012A